VALUASI EKONOMI SUMBER DAYA MANGROVE DI DUSUN BAROS DESA TIRTOHARGO KECAMATAN KRETEK KABUPATEN BANTUL - , TYAS ISMI T ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Mangrove has a significant benefit for both of ecological and social economic values, however a quantification of mangrove economic values is infrequently be done. The objective of the research is to calculate the total economic values of mangrove ecosystem. The research were carried out in Baros Beach Bantul Regency on September to October 2013. The numbers of 41 farmers, 10 fishers, 9 cattlemans and 34 tourists were interviewed to find out the economic values of mangrove ecosystem. The results was presented the total benefits of economic values in mangrove area was IDR168.744.141,67/ha/year, which consist of IDR19.756.491,67/ha/year for direct benefits, IDR132.017.160,00/ha/year for indirect benefits, IDR170.490,00/ha/year for optional benefits and IDR16.800.000,00/ha/year for existence benefits. The indirect economic benefits of mangrove area was higher. It shows that ecological functions of mangrove played a greater benefits and the act to conserve and expand the mangrove area are extremely needed. The sustainability of the mangrove and management based on ecology might remain as appropriate way to do in the future.